Periapical lesions decrease Akt serine phosphorylation and plasma membrane GLUT4 content in rat skeletal muscle - Pereira, Renato Felipe [UNESP]; de Oliveira da Mota, Max Sander [UNESP]; de Lima Coutinho Mattera, Maria Sara [UNESP]; Tsosura, Thaís Verônica Saori [UNESP]; Chiba, Fernando Yamamoto [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Ervolino, Edilson [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Okamoto, Maristela Mitiko; Machado, Ubiratan Fabres; Sumida, Doris Hissako [UNESP] (Springer Nature, 2016)
Objectives: Periapical lesion (PL) promotes insulin resistance; however, the mechanisms underlying this alteration are not fully understood. Therefore, in this study, we aimed to evaluate the Akt serine phosphorylation status and GLUT4 expression levels in the gastrocnemius muscle (GM) of rats with PL. Materials and methods: Male Wistar rats (n = 42) were distributed equally into control (CN) and PL groups. The pulpal tissue of the PL group rats was exposed to the oral environment for 30 days. Thereafter, glucose and insulin levels were assessed, followed by homeostasis model assessment of insulin resistance (HOMA-IR). The Akt serine phosphorylation and GLUT4 levels of microsomal (M) and plasma membrane (PM) fractions were evaluated by western blotting and analyzed statistically. Results: Compared to CN group rats, PL group rats had lower insulin sensitivity (as observed by HOMA-IR), lower Akt serine phosphorylation status after insulin stimulus, and lower GLUT4 levels in the PM fraction. However, the M fraction in the PL group did not differ significantly from that of the CN group. Conclusions: PL decreases insulin sensitivity, Akt phosphorylation, and PM GLUT4 content. Clinical relevance: The present study indicates that preventing endodontic disease can thwart insulin resistance.
Keywords: Diabetes mellitus; Glucose transporter type 4; Insulin resistance; Periapical lesions